Pengaruh Lingkungan Kerja, Kompensasi, dan Kompetensi terhadap Kinerja Guru di Sekolah Islam Terpadu Ash-Shiddiiqi Jambi - Muntasir Muntasir; Ekawarna Ekawarna; Sofwan Sofwan (Universitas Batanghari Jambi, 2023)
The work environment is a means or a place that influences the performance of a teacher. Compensation is a reward that is considered, so that the teacher can play an important role in carrying out his responsibilities. while competence is to manage student learning. While teacher performance is the result of work in quality and quantity that is achieved by a teacher in carrying out his duties in accordance with his responsibilities. This study aims to analyze the direct effect of the work environment on teacher performance, the direct effect of the work environment on competence, the indirect effect of the work environment on teacher performance through competence, the direct effect of compensation on teacher performance, the direct effect of compensation on competence, the indirect effect of compensation on performance teachers through competence, the direct effect of competence on teacher performance. This research was conducted at the Ash-Shiddiiqi Integrated Islamic School Jambi. The approach used in this thesis is descriptive and quantitative research with path analysis method (Path Analysis). The sample in this study was 100 respondents. The instrument used in this research is a questionnaire in the form of statement items. Then the data is processed using the SPSS Statistics 22 application. The results of this study concluded that the work environment has no effect on competence, compensation has an effect on competence, work environment has an effect on teacher performance, compensation has no effect on teacher performance, competence has no effect on teacher performance, work environment has no effect on teacher performance through competence as an intervening variable, compensation has no effect on teacher performance through competence as an intervening variable.